Cost Analysis from the Patient's Perspective and Economic Difficulties in Hemodialysis Patients at Fatmawati RSUP Jakarta - Mawaddati Rahmi; Yusi Anggriani (Budapest International Research and Critics University, 2021)
Chronic kidney disease is a global health problem with an increasing prevalence and incidence of kidney failure, has a poor prognosis and high costs. One way to overcome this high financing problem is of course by doing early treatment and for that, it is necessary to identify the risk factors of the disease. The purpose of this study was to examine the costs from the patient's perspective and the economic hardship experienced by the patient's family. The study used a case control method with a ratio of 1:1, where primary data were obtained through direct interviews with patients and/or their families. Based on the analysis, the average transportation cost required for one time hemodialysis is around Rp.12,000 - Rp.178,750, depending on vehicle type and vehicle mileage. Only 54 out of 100 hemodialysis patients need a companion with an average monthly cost of Rp.2,055,556. The cost of lost productivity per month in the study ranged fromRp.691,964 - Rp.1,942,308, depending on the patient's income. However, only 13% of patients experienced economic difficulties in the form of difficulty paying bills and daily needs. Other economic difficulties such as asking for help to selling assets were experienced by 25% of patients, and this was related to the length of time they underwent hemodialysis.